Skipped multifocal extensive spinal tuberculosis involving the whole spine: A case report and literature review. Issue 3 (January 2018) - Wu, Minhao; Su, Jiajia; Yan, Feifei; Cai, Lin; Deng, Zhouming
Abstract: Rationale: Skipped multifocal extensive spinal tuberculosis (TB) involving the whole spine is very rare. So far, only 3 cases have been reported. Patient concerns: We report a rare case of skipped multifocal extensive TB involving the whole spine of a 33-year-old Chinese male. The patient had been asymptomatic until his symptom was significantly aggravated, which caused him to have difficulty in walking and sleeping. The whole spinal computed tomography (CT) scan showed multifocal worm-eaten and osteolytic bony destruction spread over noncontiguous multilevel vertebral involvement in cervical, thoracic, lumbar, and sacral. In addition, the patient presented with low back pain, progressive fever, night sweats, and weight loss. An open biopsy was undergone indicating granulomatous inflammation after thorough radiographic examinations and laboratory investigations, which to our knowledge have been rarely reported by the published medical reference literature. Dignoses: It was initially diagnosed as lymphoma, multiple myeloma, or a metastatic disease by the radiologist. Final pathology confirmed it as an atypical form of spinal TB, which is extremely rare. Interventions: The patient with no progressive severe neurological symptoms, spinal deformity, or a huge abscess was put on a combination of anti-TB treatment and discharged in an improved state to continue medication for a total of 12 months. Outcomes: This article is a case report, no outcomes. Lessons: Multifocal extensive spinal TB involving the whole spine is rarely reported in the literature, which presents with atypical presentations and imaging features. It is noticeable that the possibility of TB is considered for any skip lesions involving the spine cautiously. Meanwhile, careful physical examination, trials of anti-TB treatment, and using the whole spine MRI routinely also play an important role in the diagnosis and treatment of this disease.